A retrospective serologic survey of hantavirus infections in the county of Cássia dos Coqueiros, State of São Paulo, Brazil Inquérito sorológico retrospectivo das infecções por hantavirus no município de Cássia dos Coqueiros, Estado de São Paulo, Brasil - Soraya Jabur Badra; Felipe Gonçalves Mota Maia; Glauciane Garcia Figueiredo; Gilberto Sabino dos Santos Junior; Gelse Mazzoni Campos; Luiz Tadeu Moraes Figueiredo; Afonso Dinis Costa Passos (Revista da Sociedade Brasileira de Medicina Tropical, 2012)
INTRODUCTION: In recent years, hantavirus infections producing severe diseases have obtained an increased attention from public health authorities from the countries of Eurasia to the Americas. Brazil has reported 1,300 cases of hantavirus cardiopulmonary syndrome (HCPS) from 1993 to 2010, with about 80 of them occurring in the northeast of the State of São Paulo, with 48% fatality rate. Araraquara virus was the causative agent of HCPS in the region. Considering that hantaviruses causing human disease in the Americas were unknown until 1993, we have looked for hantavirus infections in the population of Cássia dos Coqueiros county, northeast of the State of São Paulo, Brazil, before this time. This county has about 2,800 inhabitants and an economy based on agriculture, including cultivation of Brachiaria decumbens grass. The grass seeds are an important rodent attraction, facilitating transmission of hantavirus to man. Four HCPS cases were reported so far in the county. METHODS: In this study, 1,876 sera collected from 1987 to 1990 were tested for IgG to hantavirus by IgG-ELISA, using the N recombinant protein of Araraquara virus as antigen. RESULTS: Positive results were observed in 89 (4.7%) samples, which were all collected in 1987. The positivity among urban inhabitants was 5.3%, compared with 4.3% among those living in rural areas. CONCLUSIONS: Our results showed that hantavirus infections occurred in Cássia dos Coqueiros, completely unrecognized, even before hantaviruses were described in the Americas. INTRODUÇÃO: Infecções graves por hantavírus têm obtido crescente atenção das autoridades da saúde pública da Eurásia e Américas. De 1993 a 2010, o Brasil reportou 1.300 casos de síndrome pulmonar cardiovascular por hantavírus (SPCVH) com, aproximadamente, 80 deles no nordeste do Estado de São Paulo com taxa de fatalidade de 48%. O vírus Araraquara é o agente etiológico da SPCVH nessa região. Considerando que nas Américas as doenças em humanos causadas por hantavírus eram desconhecidas até 1993, procuramos infecções por hantavírus nas populações do município de Cássia dos Coqueiros, nordeste de São Paulo, Brasil, antes dessa data. Esse município tem 2.800 habitantes e economia baseada na agricultura, com intenso cultivo da gramínea Brachiaria decumbens. Sementes de gramíneas têm um papel importante em atrair roedores, facilitando a transmissão de hantavírus para humanos. Nesse município, até o momento 4 casos haviam sido reportados. MÉTODOS:Neste estudo, coletou-se 1.876 soros entre 1987 a 1990 e testamos para pesquisa de IgG contra hantavirus utilizando um ELISA que tem como antígeno a proteína N recombinante do vírus Araraquara. RESULTADOS: Dentre os soros analisados, 89 (4,7%) foram positivos, mostrando que esta infecção já ocorria previamente à descrição dos hantavirus americanos e deve estar ocorrendo há anos nesta região. A positividade entre os habitantes urbanos foi de 5,3% se comparado com 4,3% entre aqueles que viviam em áreas rurais. CONCLUSÕES: Nossos resultados mostraram que as infecções ocorridas por hantavirus foram completamente despercebidas em Cássia dos Coqueiros antes da descrição do hantavirus americano.